Accessibility to Cultural Heritage : Nordic Perspectives (Copenhagen : Nordic Council of Ministers, 2009)
Accessibility to cultural heritage is about consciousness, knowledge, creativity and balance Heritage has meaning only through its encounter with people. This report shows how accessibility questions are being addressed through practical examples drawn from across the Nordic countries. There are considerable variations in scale, ranging from the remote church on an island in Iceland to the baroque palace in the centre of Stockholm. Most of the cases have found their solutions, some permanent and others temporary, while others represent challenges that are still being worked on. It is important to make people aware of the various choices that have to be taken, especially when the solutions have negative consequences for the heritage. Physical accessibility can shadow for understanding and experience of the site or monument. Access to cultural heritage is too important for brutal and ill-timed solutions. Good and lasting solutions often need time to mature.